2020
DOI: 10.1016/j.fbp.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Operational considerations for hot-washing in potato crisp manufacture

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…As the focus on acrylamide became greater, attention to the detailed operation of all units in the production intensified. With previous studies on the washing stage described in Bartlett et al (2020) being effective, observations of acrylamide concentration revealed that with lowered reducing sugars, it was still possible to get high acrylamide by frying incorrectly. Attention therefore focused on the fryer control to a much greater extent and also addressed the needs of a management information system.…”
Section: Dashboard Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…As the focus on acrylamide became greater, attention to the detailed operation of all units in the production intensified. With previous studies on the washing stage described in Bartlett et al (2020) being effective, observations of acrylamide concentration revealed that with lowered reducing sugars, it was still possible to get high acrylamide by frying incorrectly. Attention therefore focused on the fryer control to a much greater extent and also addressed the needs of a management information system.…”
Section: Dashboard Developmentmentioning
confidence: 96%
“…Studies on the impact of blanching of potato strips and slices by Mestdagh et al (2008), Mariotti et al (2015) and Palermo et al (2016) described the importance of selecting the best blanching temperature and residence time. A detailed study on the blanching operation prior to the fryer considered in this paper is presented by Bartlett et al (2020) and it has been optimised for maximum sugar removal effectiveness. While many factors impact on effectiveness, a reduction of around 50% of reducing sugars is typically achieved in the blanching operation.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, blanching can reduce the colour development of fried potato slices and possibly minimise variation in colour across different potato cultivars of varying levels of glucose due to the effective removal of inherent sugars prior to frying. In fact, recent studies by Bartlett, et al [37] and Zhang, et al [41] consistently reported that extending the blanching duration further provoked changes in the microstructure of potato tissues, consequently facilitating the release of sugars and amino acids involved in Maillard reaction, and thus maximising the reduction of acrylamide of potato slices after frying.…”
Section: The Effect Of Sequential Pef and Blanching Pre-treatment On The Colour Characteristics Of Fried Potato Slicesmentioning
confidence: 99%
“…Therefore, it is expected that the high glucose content in 'Nadine' will lead to excessive colour browning in the potato slices when fried. According to Bartlett, et al [37], potato cultivar with total reducing sugars of greater than 50 mg/g is generally considered as tubers with a high acrylamide risk in any deep-fried potato products manufacturing line (e.g., French fries and potato crisp).…”
Section: Comparison On the Chemical Composition Of Four Different Potato Cultivarsmentioning
confidence: 99%
“…Frying in palm oil was performed in duplicate at 175 AE 2C in a 3 L Selection Magimix professional deep fat fryer (UK). Commercial processing condition were adopted from Bartlett et al (2020) with some modification in particular frying times were 4, 4.5 and 5.5 min for parsnip, potato and beetroot, respectively (frying times were minimized to reduce lipid oxidation while maintaining vegetable crisp quality). The oil temperature was monitored by an external probe (E.T.I food check thermometer, Sussex, UK).…”
Section: Pre-treatment and Fryingmentioning
confidence: 99%